2021
DOI: 10.1186/s13048-021-00795-z
|View full text |Cite
|
Sign up to set email alerts
|

Early stage epithelial ovarian cancer metastasis through peritoneal fluid circulation

Abstract: Background Although epithelial ovarian cancer (EOC) spreads through peritoneal circulation, all patients with clinical early-stage ovarian cancer (OC) benefit from routine surgical staging is still unclear. Methods This cross-sectional study used data from medical records of patients with clinical early-stage EOC who received complete surgical staging from 2006 to 2016 at our hospital. We excluded patients with non-epithelial OC or with stage IV di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…According to the precursor escape theory [ 29 , 30 ], benign early serous proliferation (ESP) and the later tubal intraepithelial lesion cells may escape from tubal precursor lesions and transform within the peritoneal cavity [ 17 , 29 , 31 ]. A recent study of 50 patients with early-stage EOC revealed the presence of cancer cells in the peritoneal fluid in 12 (24%) patients, and micrometastases in the peritoneum and omentum in another 10 (20%) and 8 (16%) patients, respectively [ 32 ]. Studies also showed that ESP and STIL/STIC may have been shed to the peritoneal cavity prior to the formation of overt HGSC [ 17 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the precursor escape theory [ 29 , 30 ], benign early serous proliferation (ESP) and the later tubal intraepithelial lesion cells may escape from tubal precursor lesions and transform within the peritoneal cavity [ 17 , 29 , 31 ]. A recent study of 50 patients with early-stage EOC revealed the presence of cancer cells in the peritoneal fluid in 12 (24%) patients, and micrometastases in the peritoneum and omentum in another 10 (20%) and 8 (16%) patients, respectively [ 32 ]. Studies also showed that ESP and STIL/STIC may have been shed to the peritoneal cavity prior to the formation of overt HGSC [ 17 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of peritoneal cytology with the surgical specimen results in an incomplete staging of the ovarian cancers. The prognostic significance of malignant cells in washings or brushings varies, depending on the primary ovarian lesion, for example in serous borderline tumour or serous papillary carcinoma 20,21 . Moreover, positive washing cytology may be associated with adnexal involvement of endometrial carcinoma 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic significance of malignant cells in washings or brushings varies, depending on the primary ovarian lesion, for example in serous borderline tumour or serous papillary carcinoma. 20,21 Moreover, positive washing cytology may be associated with adnexal involvement of endometrial carcinoma. 22 The significance of positive washings remains controversial for most types of uterine carcinoma, and staging for prognosis now requires histological confirmation of serosal/adnexal involvement.…”
Section: Tis Effusion Diagnostic Categoriesmentioning
confidence: 99%
“…Spread of ovarian carcinoma to the abdominal cavity usually occurs through the peritoneal circulation [63]. In order to understand how the tumor spreads within the peritoneum, it is necessary to know its anatomy and function.…”
Section: Diffusion Pathwaysmentioning
confidence: 99%